Major affective disorders in chronic obstructive pulmonary disease compared with other chronic respiratory diseases - Chaicharn Pothirat (2018)
© 2015 Pothirat et al. Background: Chronic obstructive pulmonary disease (COPD) and other chronic respiratory diseases (CRDs) have significant impacts on quality of life including psychomotor domain. Purpose: To evaluate three major affective disorders in subjects with COPD compared with other CRDs and nonill population. Materials and methods: The Thai version of Mini International Neuropsychiatric Interview (MINI) was used as a diagnostic instrument for three major affective disorders (generalized anxiety disorder, major depressive disorder, and panic disorder) by face-to-face interview in assessing patients with CRDs [COPD, asthma, rhinasthma, all asthma (asthma and rhinasthma), and chronic rhinitis], and nonill subjects. Logistic regression analyses were used to determine the relation between major affective disorders and CRDs adjusting for age, sex, and disease severity. Results: Major affective disorders were more prevalent in CRDs than nonill groups (adjusted OR =2.6 [95% CI, 1.8−3.9] , P < 0.001). COPD patients had significantly more generalized anxiety and panic disorder (adjusted OR =4.0 [95% CI, 1.4−11.9], P=0.011, and 4.4 [95% CI, 1.1−18.1] , P=0.038, respectively) but not major depressive disorder (adjusted OR =2.7 [95% CI, 0.8−9.0, P=0.105]) than nonill group. Comparing with all asthma, COPD patients had lower occurrence of major depressive and panic disorders (adjusted OR =0.1 [95% CI, 0.0−0.4] , P=0.002, and 0.1 [95% CI, 0.0−0.9], P=0.043, respectively). There was no difference in major mood disorders in COPD, rhinasthma, and chronic rhinitis patients. Major affective disorders were not increased by disease severity in COPD. Conclusion: Major affective disorders were significantly higher in CRDs than nonill population. Generalized anxiety and panic disorders were significantly high in COPD patients. Moreover, major depressive and panic disorders in COPD were significantly lower than all asthma. The prevalence of major affective disorders may not be related to severity of COPD.